Dectin-1-Syk-CARD9 Signaling Pathway in TB Immunity - Wagener, Matthew; Hoving, J. Claire; Ndlovu, Hlumani; Marakalala, Mohlopheni J. (Frontiers in Immunology, 2018)
One of the first steps toward mounting an effective immune response to Mycobacterium tuberculosis (Mtb) is recognition of the pathogen through pattern-recognition receptors (PRRs) expressed by innate immune cells. Activation of the PRR Dectin-1 by an unknown mycobacterial ligand triggers an intracellular signaling cascade involving numerous proteins, including spleen tyrosine kinase, protein kinase C-delta, and caspase recruitment domain family member 9, some of which have been shown to influence host immune response to TB infection. Here, we review the role of Dectin-1 signaling pathway in anti-mycobacterial immunity and discuss its contribution in the control of Mtb infection, and potential applications in TB vaccine adjuvanticity.